2016
DOI: 10.1186/s12245-016-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

An innovative safe anesthesia and analgesia package for emergency pediatric procedures and surgeries when no anesthetist is available

Abstract: BackgroundAdequate pain control through sedation and anesthesia for emergency procedures is a crucial aspect of pediatric emergency care. Resources for administering such anesthesia are extremely limited in many low-income settings.MethodsNon-anesthetist providers in Western Kenya were trained in the use of a ketamine-based sedation and anesthesia package for non-anesthetists, Every Second Matters for Mothers and Babies-Ketamine™ (ESM-Ketamine). Data on use and safety of this package for emergent and urgent pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…During operation process, inadequate pain control may lead to incomplete procedure and adverse complications. 1 To facilitate a higher success rate, a majority of procedures are performed under anesthetic effect, especially for uncooperative circumstances among children. 2,3 Therefore, administering an appropriate degree of anesthesia to cope with the procedural demands remains a challenge for the anesthesiologist.…”
Section: Introductionmentioning
confidence: 99%
“…During operation process, inadequate pain control may lead to incomplete procedure and adverse complications. 1 To facilitate a higher success rate, a majority of procedures are performed under anesthetic effect, especially for uncooperative circumstances among children. 2,3 Therefore, administering an appropriate degree of anesthesia to cope with the procedural demands remains a challenge for the anesthesiologist.…”
Section: Introductionmentioning
confidence: 99%
“…21 The lack of anesthesia-trained workforce in Chad is huge. Many educational interventions have been proposed to address this kind of gap, from five-day brief courses 17,32 to full training programs 10 certified by local authorities. Our program offers a reasonable alternative and might serve as a bridge solution for training nurses intensively and efficiently to provide anesthesia for common procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Despite this, no internationally validated training programs for non-physician anesthesia providers (NPAPs) have been proposed for LMIC with a wide range of designs, methodologies, and structures implemented worldwide. 10,13,17 Chad is a landlocked sub-Saharan African country. Its population is approximately 14 million people, with a per capita gross national income of 720 USD per year.…”
Section: Résumémentioning
confidence: 99%
“…described the delivery of PSA training to nurses in Uganda and showed that 191 PSA cases were safely carried out by six nurses who participated in the training. Another project of teaching and implementing a simplified protocol and checklist for ketamine for PSA has been described by Schwartz et al . Our approach was different from these projects in that we recruited local Japanese physicians to develop and deliver the training sessions.…”
Section: Discussionmentioning
confidence: 99%